Sward, bakla, gay: Language, labels, and gender roles in films, a reflection of the history of the gay community, 1978 - 2016 - Kaluag, Alexandria Jamilla Bianca C. (Animo Repository, 2021)
This thesis will analyze how language, labels, and gender roles shown in selected Philippine films reflected the realities of the gay community per decade and inadvertently captured the evolution and history of the gay community in the Philippines. This research will also study the social, cultural, economic, and political realities members of the gay community experienced from 1978 to 2016 to understand how these factors affected their portrayal in films, as well as society’s sentiment towards members of the gay community. It is imperative for Filipinos to study how filmmakers portrayed effeminate men from the seventies up to 2016 to see how these portrayals affected society’s perception on homosexuals and the gay community in the Philippines. It is also important to study the history of the gay community in the twenty-first century to increase society’s awareness and further educate society about homosexuality to prevent homophobia within the country. In the seventies, the term sward was heavily used to refer to members of the Third Sex. Despite thorough investigation, scholars were never able to establish the origin of the term sward. However, they all agree that swards believed that the use of swardspeak made them special during the seventies. This belief prompted majority of the gay community to speak swardspeak, a language that the heterosexuals do not speak or use which caused a social divide between the swards and the heterosexuals. The term bakla was soon added to the list of labels used to refer to homosexual men in the eighties. The term bakla was predominantly used as an insult to homosexuals in the country. However, Dr. Ronald Baytan believe that it is possible that homosexuals neutralized this word and turned it from something that triggers oppression into something that causes self-affirmation or “transgressive reinscription”. Much like the term bakla, the term gay was introduced to society during the nineties. However, this was only used by gay men with middle to high-income, those who belonged in the lower social prompted to use the term bakla. The following films were used as the primary sources in this research: Ang Tatay Kong Nanay (1978), Manila By Night (1980), Pusong Mamon (1998), Ang Pagdadalaga ni Maximo Oliveros (2005), and Die Beautiful (2016). These films were selected because they were able to capture and reflect the social, cultural, economic, and political realities the gay community experienced per decade from 1978 to 2016.